2022
DOI: 10.3389/fimmu.2022.967737
|View full text |Cite
|
Sign up to set email alerts
|

Distinct responses of newly identified monocyte subsets to advanced gastrointestinal cancer and COVID-19

Abstract: Monocytes are critical cells of the immune system but their role as effectors is relatively poorly understood, as they have long been considered only as precursors of tissue macrophages or dendritic cells. Moreover, it is known that this cell type is heterogeneous, but our understanding of this aspect is limited to the broad classification in classical/intermediate/non-classical monocytes, commonly based on their expression of only two markers, i.e. CD14 and CD16. We deeply dissected the heterogeneity of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
6
8
1
Order By: Relevance
“…While some clusters occupied definite positions on the UMAP, the Mϕ populations expressing high levels of lineage markers (Mϕ, CD68 hi Mϕ, CD14 hi /CD16 hi Mϕ and CD163 hi Mϕ) were closer and overlapping, suggesting that they might represent the same population at different maturation states ( Fig. 3F ), confirming previous evidence obtained by trajectory analyses of transcriptomic data ( 36, 37 ). By UMAP visualization of the cluster arrangement with respect to their tissue location ( Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…While some clusters occupied definite positions on the UMAP, the Mϕ populations expressing high levels of lineage markers (Mϕ, CD68 hi Mϕ, CD14 hi /CD16 hi Mϕ and CD163 hi Mϕ) were closer and overlapping, suggesting that they might represent the same population at different maturation states ( Fig. 3F ), confirming previous evidence obtained by trajectory analyses of transcriptomic data ( 36, 37 ). By UMAP visualization of the cluster arrangement with respect to their tissue location ( Fig.…”
Section: Resultssupporting
confidence: 86%
“…The regional specialization of macrophage subtypes in tumor tissues is an important feature that can control their functional profile and correlate with survival benefit, as shown in melanoma ( 47 ) and in human colo-rectal liver metastasis ( 37 ). In line with previous studies, a considerable fraction of the Mϕ granularity was accounted by very similar populations (occupying the same position on a UMAP representation), possibly representing the same cell in different maturation states ( 36, 37 ). Another interesting aspect emerging from the integrative analysis was that tumor cells were significantly more frequent in poorly fibrotic tumors, while the presence of fibrosis did not correlate with the K score (i.e., the distribution pattern of tumor cells).…”
Section: Discussionsupporting
confidence: 90%
“…Totally, we sequenced 20890 cells, which decreased to 19085 after quality control. Dimensionality reduction by UMAP ( 26 ) clearly demonstrated a net segregation of the NC/slan + /slan − - and CL-monocyte groups, with INT-monocytes placing exactly in between them ( Figures 4A, B ), as expected ( 8 , 12 , 27 , 28 ). Moreover, in line with the bulk transcriptomic ( Figure 2A ) and proteomic ( Figure 3A ) results, the same UMAP confirmed that slan − /NC-monocytes stand closer to CL-and INT-monocytes than to slan + /NC-monocytes ( Figures 4A, B ).…”
Section: Resultssupporting
confidence: 69%
“…Ym1 + Mos were deemed crucial for inflammation resolution, simultaneously producing higher levels of anti-inflammatory IL-10 and lower pro-inflammatory cytokines (IL-6, IL-12) than Ym1 − monocytes. NeuMos were also discovered to be present in the steady-state BM and blood [ 30 , 31 ], perhaps suggesting the presence of a background signal that maintains a basal level differentiation of GMPs into NeuMos in the BM. On the other hand, a deviation of GMP differentiation into cMoPs into a unique progenitor state could also occur in particular diseases such as bleomycin-induced fibrosis, whereby cells termed segregated-nucleus-containing atypical monocytes (SatMs) were discovered [ 32 ].…”
Section: Monocyte Development: Different Fates Before Birthmentioning
confidence: 99%
“…However, many questions still remain: How do these circulating phenotypes differ from monocytes that arise through the priming of BM progenitors such as NeuMos and DCMos? In a recent study, Rigamonti et al have attempted to address this question by demonstrating nine distinct functional populations of human circulating monocytes in healthy donors [ 31 ]. Specifically, there were five populations related either to inflammatory, neutrophil-like, interferon-related, or platelet-related pathways among the classical subset of monocytes.…”
Section: Monocyte Reservoirs In the Periphery: Strategically Position...mentioning
confidence: 99%